Performance Audit of Internal Control System in Health Department in Manipur - CAG of India (CAG of India, 2008)
Internal control system is a process by which an organisation directs its activities to achieve its objectives. Such a system consists of methods, systems and procedures for protecting resources from waste, loss, theft, misuse or mismanagement and provides reasonable assurance that the organizational goals and objectives are achieved. This performance audit presents an evaluation of the internal control system in the Health Department in Manipur for the period 2002-2007. The performance audit revealed deficiencies in its budgetary, financial, administrative and supervisory controls, non maintenance of basic records and non- reconciliation of expenditure. Internal audit arrangements were also deficient and unable to provide assurance against possibilities of financial irregularities. These lapses adversely affected delivery of primary health care services in the State.
For the Period 2002-03 to 2006-07